Pitch perception deficits in nonverbal learning disability. (December 2016) - Fernández-Prieto, I.; Caprile, C.; Tinoco-González, D.; Ristol-Orriols, B.; López-Sala, A.; Póo-Argüelles, P.; Pons, F.; Navarra, J.
Highlights: Nonverbal learning disability patients present difficulties in spatial reasoning. Difficulties in categorizing auditory frequencies are observed in NLD patients. A deficit in pitch processing could underlie impairments in other cognitive areas. Abstract: The nonverbal learning disability (NLD) is a neurological dysfunction that affects cognitive functions predominantly related to the right hemisphere such as spatial and abstract reasoning. Previous evidence in healthy adults suggests that acoustic pitch (i.e., the relative difference in frequency between sounds) is, under certain conditions, encoded in specific areas of the right hemisphere that also encode the spatial elevation of external objects (e.g., high vs. low position). Taking this evidence into account, we explored the perception of pitch in preadolescents and adolescents with NLD and in a group of healthy participants matched by age, gender, musical knowledge and handedness. Participants performed four speeded tests: a stimulus detection test and three perceptual categorization tests based on colour, spatial position and pitch. Results revealed that both groups were equally fast at detecting visual targets and categorizing visual stimuli according to their colour. In contrast, the NLD group showed slower responses than the control group when categorizing space (direction of a visual object) and pitch (direction of a change in sound frequency). This pattern of results suggests the presence of a subtle deficit at judging pitch in NLD along with the traditionally-described difficulties in spatial processing.